Retinal Tacks for Complicated Retinal Detachment: Retinal Tacks in the Times of Modern Small-Gauge Vitrectomy. (31st March 2022) - Mautone, Luca; Dulz, Simon; Skevas, Christos; Schultheiss, Maximilian; Spitzer, Martin Stephan
Abstract : Purpose . To investigate the efficacy and safety profile of retinal tacks (RTs) in cases of retinal detachment (RD) with advanced proliferative vitreoretinopathy (PVR). Materials and Methods . In this single-center, retrospective study medical record, optical coherence tomography and ultra-widefield fundus images of patients with complex PVR-related and RT surgery were reviewed. All cases underwent 23G pars plana vitrectomy (PPV), RT implantation, retinectomy, circumferential intraoperative laser retinopexy, and silicone oil tamponade. Results . Fourteen eyes of 14 patients with complex rhegmatogenous RD with PVR were included: 7 cases showed PVR grade C type P and 7 combined grades A and P. RTs were positioned at contracted, stiffened retinal areas to achieve attachment of retinectomy borders after extensive PVR peeling. Patients underwent on an average of 1.3 PPVs (range 0–3) prior RT surgery. An average of 2.5 RTs (range 1–4) were implanted. Only in a single eye, a recurrent RD occurred. In 10 eyes, the silicone oil tamponade was still in place at the last follow-up. In 5 eyes, the silicone oil could be removed without redetachment in all of these cases (average of 31.3 weeks, range 11.4–53). No RT-related intraoperative or postoperative complications like dislocation or bleedings were observed. Conclusion . RTs have the potential to improve the treatment of complex PVR-associated RD. RT can be a useful surgical tool to reattach borders of retinectomies in advanced PVR. No RT-associated complication were observed in this study.